Nanobotany: An Important Line of Research for Botanists - Maiti, Ratikanta; Thakur, Ashok K.; Sarkar, N. C. (International Journal of Economic Plants, 2015)
Nanotechnology has opened many new avenues for the researchers in various fields of science and technology. In biological sciences, it has widened scope for scientists and researchers and a number of applications have been invented. Significant research advances have been undertaken on the use of nanoparticles in various disciplines of botany. Nanoparticles are used to study the physiology of plants and several industrial uses….